PENGARUH FINANCIAL DISTRESS, PERGANTIAN MANAJEMEN DAN PERTUMBUHAN PERUSAHAAN TERHADAP AUDITOR SWITCHING - Ni Kadek Rina Mita Dewi; Ni Ketut Muliati (UNHI Press, 2021)
Auditor switching is a change of auditors carried out by a company either compulsory or voluntarily. This study aims to examine how the effect of financial distress, change of management and company growth on auditor switching in manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2019. The population of this study is manufacturing companies on the Indonesia Stock Exchange 2015-2019, namely 169 companies . This type of research is quantitative and the sampling technique uses purposive sampling method, so that the sample obtained is 420 samples from 84 companies. The analysis method used in this research is logistic regression analysis. Based on the results of the analysis test, it was found that financial distress and management changes had no significant effect on auditor switching. Meanwhile, company growth has a positive and significant effect on auditor switching.